The dragonfly effect : quick, effective, and powerful ways to use social media to drive social change - Aaker, Jennifer Lynn (Jossey-Bass, 2010)
"Proven strategies for harnessing the power of social media to drive social change Many books teach the mechanics of using Facebook, Twitter, and YouTube to compete in business. But no book addresses how to harness the incredible power of social media to make a difference. The Dragonfly Effect shows you how to tap social media and consumer psychological insights to achieve a single, concrete goal. Named for the only insect that is able to move in any direction when its four wings are working in concert, this book. Reveals the four "wings" of the Dragonfly Effect-and how they work together to produce colossal results. Features original case studies of global organizations like the Gap, Starbucks, Kiva, Nike, eBay, Facebook; and start-ups like Groupon and COOKPAD, showing how they achieve social good and customer loyalty. Leverage the power of design thinking and psychological research with practical strategies. Reveals how everyday people achieve unprecedented results-whether finding an almost impossible bone marrow match for a friend, raising millions for cancer research, or electing the current president of the United States. The Dragonfly Effect shows that you don't need money or power to inspire seismic change."--